Occurrence and distribution of enlA gene in clinical isolates of Enterococcus faecalis according to isolates sources - Mahmood Ra'oof, Wa'ad; Hussein Ali, Aisha (Tikrit Journal of Pharmaceutical Sciences, 2023)
Enterolysin A, is a cell wall-degrading bacteriocin (metalloendopeptidase) secreted by some E faecalis strains which can kill a wide range of bacteria and on of virulence factors of this bacterium.The prevalence of enlA gene in E. faecalis isolated from clinical sources in our country is not studied. So the present study was performed to determine the prevalence of enlA gene in E. faecalis isolated from different types of infections and the distribution of this gene among these isolates according to infection site. The present study was conducted on Forty two clinical isolates of Enterococcus faecalis isolated in a previous study from patients attending Tikrit Teaching Hospital in Tikrit city, Iraq, with GIT , UTI ,vaginal, wound and burn infections which were re-identified according to microscopic, macroscopic and biochemical tests.Enterolysin A structural gene was determined in E. faecalis isolates by specific primer (EN1EF1:TTC TTC TTA TTC TGT CAA CGC AGC , ENIER1:GAC TGT GAA ATA CCT ATT TGC AAGC) using PCR technique.The results of PCR for enlA gene (the gene responsible for cell wall hydrolyzing activity) showed that (16.6%) of E. faecalis isolates possess this gene ,since gel electrophoresis results showed DNA bands with molecular size 960bp in comparison with DNA marker. According to the distribution of enlA gene of E.faecalis isolates in respect to isolates sources, the results showed that this gene was detected in 1(14.3%) of vaginal isolates, 1(10%) of urine isolates, 5(35.7%) of stool isolates, and no of wound and burn isolates were harbor this gene. No literatures concerning the distribution of enlA gene according to sources of infections were available for comparison. So from our results we can concluded that the distribution of this gene is low in clinical isolates of E. faecalis, while it is important in stool isolates for competition of this bacterium with intestinal normal flora and colonization.